Pengaruh Labelisasi Halal, Pelayanan Islami dan Brand Image Terhadap Keputusan Pembelian (Studi Kasus Sate Apaleh Kabupaten Bireuen) - Fuadi; Zanti, Marni; Damanhur; Falahuddin; Hasan, Nazli (Jurnal EMT KITA, 2024)
This study aims to see the effect of Halal Labeling, Islamic Services and Brand Image on Purchasing Decisions (Case Study of Sate Apaleh Geurugok, Bireuen Regency). The data used in this study is primary data, amounting to 115 respondents who are customers of Sate Apaleh. The method used to analyze the relationship between variables is multiple linear regression analysis. The results showed that halal labeling has a positive and significant effect on consumer purchasing decisions on Sate apaleh, Islamic services have a positive and significant effect on consumer purchasing decisions on Sate apaleh, brand image has a positive and significant effect on consumer purchasing decisions on Sate apaleh, so it can be concluded that H3 is accepted. Overall Halal Labeling, Islamic Services and Brand Image on Purchasing Decisions (Case Study of Sate Apaleh, Bireuen Regency).